Study on the effect of temperature on the leaching of contaminants from Ballangen Tailings Deposit, Norway-A statistical method - Yuan, Fuqing; Lu, Jinmei (IOP Conference Series: Earth and Environmental Science, 2019)
Temperature is one important factor that affects the leaching of contaminants from tailings deposit. However, randomness issue due to the precision of the instrument, the variation of ambient temperature, the individual skill of the lab technician etc., is inevitable and will affect the results when we evaluate the dependence of two parameters. In this study, a statistical method was developed to analyze the experimental data to reduce randomness. The experiment data from a laboratory batch leaching experiment on the tailings at Ballangen deposit, Northern Norway were used to analyze the dependency of concentrations of Cr, Cu, Ni and Zn in the leachate on temperature. The dependency of concentrations of Cr, Cu, Ni and Zn in the leachate is determined by testing the significance of the slope coefficient of regression analysis. The results show that the concentrations of Cr and Zn do not show dependency on the temperature. However, the temperature shows evident impact on the concentrations of Cu and Ni. High temperature will produce higher Cu and Ni concentration in the leachate.